KEUNGGULAN ORGANISASI DENGAN BERTUMPU PADA SUMBER DAYA MANUSIA - Susanti, Retno (Universitas Slamet Riyadi, 2011)
ABSTRACT Humans are important factors in any organizational system developed for a role as HR which occupies a strategic as well operational functions within the organization. The system in question is the procedures and management practices, including recruitment, development, maintenance, and utilization of human resources. In order to excel in competition's organization needs to perform appropriate steps in managing human resource systems ranging from recruitment, development, maintenance, up to the utilization or utilization. Although better management practices will have a chance of a larger organization with success in the future, but also not always guarantee the success of the organization in the future, because there are many factors both internally and externally that not everything is under control of the managers. Keywords: superior organization, human resources, empowerment, the recruitment process